Integrasi Nilai-Nilai Al-Qur’an dalam Pengembangan Sumber Daya Manusia Unggul Menuju Indonesia Emas 2045 - Abdul Muhyi; Nur Arfiyah Febriani (Lembaga Yasin AlSys, 2026)
Although the development of high-quality human resources has become a central focus of various national policies toward Indonesia Emas 2045, studies that specifically integrate Al-Qur’an values as a philosophical and ethical foundation within the framework of national human resource development remain relatively limited. This study aimed to interpret and analyze the fundamental values of Al-Qur’an that are relevant to the development of high-quality human resources who are competitive, virtuous, and possess strong integrity in the context of the Indonesia Emas 2045 vision. The study employed a qualitative approach with a library research design and normative-philosophical thematic analysis by examining relevant Qur’anic verses and national policy documents, particularly the Rencana Pembangunan Jangka Panjang Nasional (RPJPN) 2025–2045. Data were collected using documentation techniques and analyzed through normative-philosophical thematic analysis. The findings show that the prescriptive values of Al-Qur’an encompass three main dimensions in developing high-quality human resources: the intellectual dimension, which emphasizes the pursuit of knowledge and innovation (Q.S. Az-Zumar [39]: 9); the character and ethical dimension, which focuses on the formation of noble character and integrity (Q.S. Al-Qalam [68]: 4); and the socio-economic dimension, which underscores the principles of collaboration and social justice (Q.S. Ali Imran [3]: 103). These findings contribute to the development of a concept of high-quality human resources grounded in prophetic Islamic values and broaden understanding of the integration between religion and national development policy. The study concludes that integrating Al-Qur’an values into educational curricula that combine religious knowledge with science and technology (STEM), alongside strengthening the role of Islamic educational institutions as strategic actors, is essential for producing intelligent, adaptive, and highly principled human resources. The implications of this study include theoretical contributions to the literature on human resource development based on Islamic values and practical implications for government and educational institutions in formulating human resource development policies and strategies toward Indonesia Emas 2045, while also opening opportunities for further research on the empirical implementation of Al-Qur’an value integration in Indonesia’s education and human resource development systems.